Impact of vacuum and nitrogen annealing on HVE SnS photoabsorber films. (15th November 2017) - Naidu, Revathi; Loorits, Mihkel; Kärber, Erki; Volobujeva, Olga; Raudoja, Jaan; Maticiuc, Natalia; Bereznev, Sergei; Mellikov, Enn
Abstract: Researchers worldwide focus on new earth abundant and cheap absorber materials for use in thin film solar cells that allow wider use of photovoltaics in energy production. SnS is one of such promising absorber materials that comprises earth abundant elements (Sn, S). We describe here the effect of annealing of high vacuum evaporated (HVE) SnS thin films in vacuum and nitrogen atmosphere with relatively high pressures of nitrogen. SnS thin films with a thickness of 500 nm were deposited onto the surface of glass by HVE at a substrate temperature of 300 °C. The as-deposited SnS thin films were annealed at 500 °C and 550 °C for 1 h in vacuum as well as in nitrogen with respect to ambient (N2 ) pressure that varied in the range of 500–2000 mbar. We analyze crystalline quality, crystal structure, elemental and phase compositions, and electrical properties of SnS films before and after the annealing process and their changes. Our results show that the use of pressurized inert ambient, such as nitrogen, improves the crystalline quality as well as the electrical properties of SnS thin films. The enhanced growth of crystals and modification of microstructural properties of SnS thin films as a function of annealing conditions (type of ambient, annealing temperature and ambient pressure) are discussed in detail.